Experimental and clinical ground of osteotropic material "Easy-Graft" using at generalized periodontitis - Dmitrieva E.O. (Морфологія, 2013)
The comparative analysis a quantitative morphological estimation of regenerative processes in osteal tissue in model of osteal defect is carried out at implantation of material "EasyGraft" (Germany) and amorphous calcium phosphate (НПП "Кергап", Ukraine) at this work. It was investigated dynamics of clinical indicators at patients after used material "EasyGraft" account severity level and character of a current of pathological process, and also a sex and age of patients. It was shown, that at patients with generalized periodontitis ІІ-ІІІ severity level of application a material "EasyGraft“ gives essential clinical advantages in comparison with amorphous calcium phosphate in the remote period of observation. The comparative estimation of efficiency in surgical treatment is spent at use investigated osteotropic materials.